Nutrition and stroke: current state and future perspectives - Mohamed, Wael Mohamed Yousef (Springer, 2024)
This book provides a thorough examination of the correlation between nutrition and stroke. It delves into the interplay between nutrition and brain functions, neurogenesis, and cognitive functions. Additionally, it investigates how various types of nutrition relate to stroke. Moreover, it discusses recent progress in recognizing the significant therapeutic role of different nutrients in addressing stroke. Finally, it offers an overview of nutrients as neuroprotective agents and outlines the fundamental principles of nutrigenomics.